The A-Z encyclopedia of food controversies and the law - Williams, Elizabeth M. (Elizabeth Marie) 1950-; Carter, Stephanie J. (Gale virtual reference library, 2011)
Covering food and law, this encyclopedia surveys laws related to organics, obesity, and fair trade.